On the Use of Special Bilinear Functions in Computing Bernoulli Polynomials - Awin, Ali M. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
In this paper we review, firstly, the subject of bilinear functions in connection with the convolution of two n-tuples vectors(originally named quacroms); then we summarize some of its important applications such as the calculation of the product of two polynomials and hence twoÂ integers and their use in representing certain quantities .The main topic of this paper is the use of these special bilinear functions in computing special functions as in the case of Bernoulli polynomials throughÂ simple recurrence relations ,this will be performed next and where the related algorithm will be described .Moreover, the first few Bernoulli polynomials are tabulated for the interval